2000
DOI: 10.1103/physreve.61.1692
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of highly asymmetric binary mixtures: A study of the role of attractive forces from the effective one-component approach

Abstract: The phase diagram of an asymmetric solute-solvent mixture is investigated at the level of the effective one-component fluid. The solvent is taken into account by computing the potential of mean force between solute particles at infinite dilution for different models of solvent-solvent and solute-solvent short range interactions. Fluid-fluid and fluid-solid coexistence lines are determined from the free energy in the reference hypernetted chain theory for the fluid branch and from a variational perturbation the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 77 publications
2
28
0
Order By: Relevance
“…The accuracy of the hybrid method was shown in Ref. [15] for the fluid-solid (FS) and fluid-fluid (FF) transitions, by comparison with the simulation data of Dijkstra et al [6], and confirmed more recently by simulations from our group [17] for the FF transition. Concerning a possible solid-solid (SS) transition between two solid states with different densities, it was shown in [26] that the perturbation treatment is suitable to describe a dense solid near close packing but is more problematic for a "softer" one with lower density.…”
Section: ͑5͒supporting
confidence: 55%
See 3 more Smart Citations
“…The accuracy of the hybrid method was shown in Ref. [15] for the fluid-solid (FS) and fluid-fluid (FF) transitions, by comparison with the simulation data of Dijkstra et al [6], and confirmed more recently by simulations from our group [17] for the FF transition. Concerning a possible solid-solid (SS) transition between two solid states with different densities, it was shown in [26] that the perturbation treatment is suitable to describe a dense solid near close packing but is more problematic for a "softer" one with lower density.…”
Section: ͑5͒supporting
confidence: 55%
“…Since it is expected to operate at the scale D s of the small (solvent) particles, it falls in the category described by model (2). This is the situation more often considered in the papers discussing the non-HS interactions effect in colloidal suspensions [14][15][16][17].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Interestingly, our estimates for the criticalη s values lie much closer than those of ref. [3] to the results of a computation using integral equation theory of both the depletion potential and its phase behaviour [34]. In ref.…”
Section: Critical Regionmentioning
confidence: 99%